Prevalence and symptom of ossification of posterior longitudinal ligaments in the Japanese general population - Sasaki, Eiji; Ono, Atsushi; Yokoyama, Toru; Wada, Kanichiro; Tanaka, Toshihiro; Kumagai, Gentaro; Iwasaki, Hiroki; Ishibashi, Yasuyuki; Takahashi, Ippei; Umeda, Takashi; Nakaji, Shigeyuki (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2014)
Ossification of the posterior longitudinal ligaments (OPLL) causes myelopathy with progression or trauma. Most OPLL patients visit the hospital after severe symptoms occur, and surgery did not supply complete relief in severe symptoms related to OPLL. While it is necessary to diagnose OPLL early and observe carefully, the nature of symptoms and asymptomatic OPLL have been unclear. The purposes of this study were to investigate the prevalence and symptoms of ossification of the posterior longitudinal ligaments (OPLL) of the cervical spine in the general population. The subjects were 1291 Japanese general residents. Radiographic OPLL was detected by lateral view of the cervical spine, and subjects were classified into OPLL and non-OPLL groups. Visual analog scales of neck stiffness, neck pain, arm pain, and the Japanese Orthopaedic Association Cervical Myelopathy Evaluation Questionnaire were examined. Neck and arm symptoms were compared among the presence of OPLL, and among subtypes (continuous, segmental, and mixed types) statistically. Prevalence of OPLL was 3.7 % in overall participants, 3.9 % in symptomatic participants, and 2.2 % in asymptomatic participants. While 86.7 % of participants with OPLL had symptoms, the consultation rate was only 6.7 %. The female OPLL group had higher neck pain than the non-OPLL group, and neck function of JOACMEQ in the continuous type of OPLL was significantly restricted compared to those without OPLL and with the mixed type of OPLL. Prevalence of OPLL was 3.7 %, and most of them had neck and arm symptoms; however, they did not visit hospitals. Asymptomatic OPLL had the potential risk for spinal cord injury and myelopathy. Early detection and careful observation would prevent the severe symptoms induced by OPLL.